Identifying the types and functions of Iranun woven textiles in Sabah - Jaafar Manap, Juita; Abd Aziz, Arba’iyah; Anwar, Rusmadiah (Faculty of Art and Design, 2025)
The people of Iranun, who inhabit the river mouths and coastal sections of Sabah, are well-known for the strong sense of family and community that they exhibit within their settlements, which are defined geographically. Their culture draws a lot of its significance from their discipline, especially through their art. As much as Iranun culture is valuable, there have been very few studies about their art and, more specifically, their weaving. Therefore, this is one of the fields that have not been investigated to any great extent, and there is little understanding of the role of this craft in the Iranun community and the surrounding local textile industry. The lack of textile studies only serves the textile industry in Iranun communities and does not serve the field in general. To fill this gap, this present study attempts to investigate and categorise the types and functions of Iranun woven textiles. A qualitative approach is used by means of ethnographic observations and semi-structured interviews with 12 respondents, including two master weavers. Results indicate that Iranun weavings are not only infused with symbolism that functions as a marker of identity and history but also community. The study stresses the need for the elements of this heritage to be preserved as they promote the local textile industry and even evoke the interest of scholars. Among the suggestions are those initiatives which are directed to cover the Iranun weaving practice and its art for cultural exhibitions and to excite the younger generation to practice the tradition. This study is part of the more extensive debate on preserving cultures and justifying why much effort is needed to protect the artistry of the Iranun people.